Suggesting the Semiotics of the Qur'an: Critical Study of Muhammad Arkoun's Revelation Reason - Mukhtar, Mukhtar; Rahman, Rahman; Khairuddin, Khairuddin; Wasalmi, Wasalmi; Suhaimi, Suhaimi; Usman, Usman (Jurnal Adabiyah, 2025)
Muhammad Arkoun, a controversial liberal Muslim figure, has attracted the attention of many researchers with his innovative approach to understanding revelation through semiotic analysis. This research aims to critically analyse how Arkoun reads Qur'anic texts using a semiotic approach, as well as its impact on religious understanding. The research method used is descriptive qualitative with a critical analysis approach, which combines eclectic approaches, postmodernism, and tafsir science. The results show that Arkoun tries to subjugate the Qur'an within the framework of linguistic analysis that is heavily influenced by western thought. With this approach, he ignores classical and contemporary Islamic methodologies, preferring to focus on the western intellectual way of thinking that separates revelation from its transcendence dimension. Arkoun argues that the reading of the Qur'an should follow global intellectual dynamics, although his views are widely considered incompatible by more conservative circles. This study hopes that Arkoun's thought can provide a new perspective for Muslim academics in the West, especially in criticising the theoretical paradigm imposed by the Western intellectual tradition. However, for ordinary people who study religion with a simpler understanding, Arkoun's thinking tends to be regarded as a dangerous theological heresy. الملخص استقطب محمد أركون، وهو شخصية مسلمة ليبرالية ليبرالية مثيرة للجدل، اهتمام العديد من الباحثين بمنهجه المبتكر لفهم الوحي من خلال التحليل السيميائي. يهدف هذا البحث إلى تحليل نقدي لكيفية قراءة أركون للنصوص القرآنية باستخدام المنهج السيميائي، وكذلك أثره على الفهم الديني. ومنهج البحث المستخدم هو المنهج الوصفي الكيفي مع منهج التحليل النقدي الذي يجمع بين المناهج الانتقائية وما بعد الحداثة وعلم التفسير. وتظهر النتائج أن أركون يحاول إخضاع القرآن في إطار التحليل اللغوي المتأثر بشدة بالفكر الغربي. وهو بهذا المنهج يتجاهل المنهجيات الإسلامية الكلاسيكية والمعاصرة، مفضلاً التركيز على الطريقة الفكرية الغربية في التفكير التي تفصل الوحي عن بعده المتعالي. يجادل أركون بأن قراءة القرآن يجب أن تتبع الديناميات الفكرية العالمية، على الرغم من أن آراءه تعتبرها الأوساط الأكثر تحفظًا غير متوافقة على نطاق واسع. وتأمل هذه الدراسة أن يقدم فكر أركون منظورًا جديدًا للأكاديميين المسلمين في الغرب، خاصة في نقد النموذج النظري الذي يفرضه التقليد الفكري الغربي. ومع ذلك، بالنسبة للأشخاص العاديين الذين يدرسون الدين بفهم أبسط، يميل فكر أركون إلى اعتباره بدعة لاهوتية خطيرة. Abstrak Muhammad Arkoun, seorang tokoh Muslim liberal yang kontroversial, menarik perhatian banyak peneliti dengan pendekatannya yang inovatif dalam memahami wahyu melalui analisis semiotika. Penelitian ini bertujuan untuk menganalisis secara kritis bagaimana Arkoun membaca teks-teks al-Qur’an dengan menggunakan pendekatan semiotika, serta dampaknya terhadap pemahaman keagamaan. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan analisis kritis, yang memadukan pendekatan eklektik, postmodernisme, dan ilmu tafsir. Hasil penelitian menunjukkan bahwa Arkoun mencoba menundukkan al-Qur’an dalam kerangka analisis linguistik yang sangat dipengaruhi oleh pemikiran barat. Dengan pendekatan ini, ia mengabaikan metodologi klasik dan kontemporer Islam, lebih memilih untuk fokus pada cara berpikir intelektual barat yang memisahkan wahyu dari dimensi transendensinya. Arkoun berargumen bahwa pembacaan al-Qur’an harus mengikuti dinamika intelektual global, meskipun pandangannya ini banyak dianggap tidak sesuai oleh kalangan yang lebih konservatif. Penelitian ini mengharapkan agar pemikiran Arkoun dapat memberi perspektif baru bagi akademisi Muslim di Barat, khususnya dalam mengkritisi paradigma teori yang dipaksakan oleh tradisi intelektual Barat. Namun, bagi masyarakat awam yang mendalami agama dengan pemahaman yang lebih sederhana, pemikiran Arkoun cenderung dianggap sebagai bid’ah teologis yang berbahaya.